Embedded indexing with Word. Part 6 – sorting and export of entries. (1st September 2021) - Greulich, Walter
Abstract : This series of articles on embedded indexing with Word concludes with two topics that are particularly important for all indexes: sorting and exporting the entries. How can you easily switch between alphabetical sorting and sorting by page numbers? Is it possible to implement letter-by-letter sorting? Directly related to these problems is the question of exporting the index entries into a format understood by Excel or dedicated indexing programs. The first five articles in the series can be found in the June, September and December 2020 issues and in the March and June 2021 issues of The Indexer (38 (2), 38 (3), 38 (4), 39 (1), 39 (2)).